2021
DOI: 10.1111/aphw.12269
|View full text |Cite
|
Sign up to set email alerts
|

“Watching the tsunami come”: A case study of female healthcare provider experiences during the COVID‐19 pandemic

Abstract: As health systems rapidly respond to COVID‐19, it is unclear how these changes influence the experiences and well‐being of female healthcare providers (FHCPs), including the potential for FHCPs to develop compassion fatigue and secondary traumatic stress. We conducted qualitative interviews ( n = 15) with FHCPs at three locations (Washington, California, and New York). Interviews explored FHCP's perspectives on how care delivery changed, processes of information delivery and decision‐mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 43 publications
(40 reference statements)
1
21
0
Order By: Relevance
“…Similar to our quantitative data, Austin et al [ 18 ], in a small qualitative study, reported the conflicting feelings of female healthcare professionals while providing care, managing information and decisions, and balancing roles, coping and well-being. Also comparable to our investigation, high stress levels in 32% of general practitioners were reported by Dutour et al [ 19 ].…”
Section: Discussionsupporting
confidence: 86%
“…Similar to our quantitative data, Austin et al [ 18 ], in a small qualitative study, reported the conflicting feelings of female healthcare professionals while providing care, managing information and decisions, and balancing roles, coping and well-being. Also comparable to our investigation, high stress levels in 32% of general practitioners were reported by Dutour et al [ 19 ].…”
Section: Discussionsupporting
confidence: 86%
“…Findings from this study may shed light into the influence of organisational culture on the expression and awareness of emotions. Moreover, the transition to telehealth during the pandemic also increased social isolation which may pose a risk to HCPs’ psychological well-being by decreasing social supports that were more abundant prepandemic 38. The aforementioned factors highlight the need to reduce potential stigma regarding mental health in healthcare settings and increase social support across a range of healthcare settings.…”
Section: Discussionmentioning
confidence: 99%
“…While it is unclear exactly why this is, some researchers hypothesize this may be due to the gendered design of PPE to fit larger body types, which are less likely to fit women HCWs. A 2021 study noted that women HCWs also face the challenge of managing multiple roles, such as HCW, partner, parent, and academic while working during the pandemic ( Austin et al, 2021 ). While many of the traditional household responsibilities often fell on women before the pandemic, Austin et al (2021) found that this imbalance of gender roles has increased significantly during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…A 2021 study noted that women HCWs also face the challenge of managing multiple roles, such as HCW, partner, parent, and academic while working during the pandemic ( Austin et al, 2021 ). While many of the traditional household responsibilities often fell on women before the pandemic, Austin et al (2021) found that this imbalance of gender roles has increased significantly during the COVID-19 pandemic. This gender divide may also lead to long term implications for future career potential as this HCW described the negative impact on her role as an academic during COVID-19:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation